ANALYSIS OF CONTENT MARKETING AND CREDIBILITY STRATEGIES ON THE GROWTH OF UMKM BUSINESS IN MEDAN CITY - Bunga Aditi (CV. Radja Publika, 2025)
The main indicators that make MSMEs experience many losses to the point of bankruptcy, including consumer demand for the product is decreasing, then the regulations and policies issued by the government do not provide direct benefits in developing MSMEs so that they are not felt directly by the community, especially Micro, Small and Medium Enterprises (MSMEs) who have to close for a long time. The purpose of this studyreview and analyze Online Marketing Strategies and Credibility in Reducing Bankruptcy of MSMEs in Medan City.This study uses a data analysis method using SmartPLS software. The results of the study showContent marketing has a significant effect on Credibility. Credibility does not have a significant effect on Business Growth. Credibility as an intervening variable has a significant impact in increasing the influence of Content marketing on Business Growth.